Oedipus the King: A Greek Tragedy, Philosophy, Politics and Philology - Nikolarea, Ekaterini (TTR, 1994)
AbstractOedipus the King: A Greek Tragedy, Philosophy, Politics and Philology — This study tries to show that the abundance of translations, imitations and radical re-interpretations of a genre like tragedy is due to various social discourses of target societies. Taking as an example Sophocles' Oedipus the King, the acclaimed tragedy par excellence, this essay discusses how the discourses of philosophy, politics and philology influenced the reception of this classical Greek tragedy by the French and British target systems (TSs) during the late 17th and early 18th century and the late 19th and early 20th century. The first section shows how, by offering Sophocles' Oedipus the King as a Greek model of tragedy, Aristotle's Poetics has formed the Western literary criticism and playwriting. The second section attempts to demonstrate why three imitations of Oedipus by Corneille (Oedipe), Dryden {Oedipus) and Voltaire {Oedipe) became more popular than any other contemporary "real" translation of the Sophoclean Oedipus. The third and final part holds that the observed revival of Oedipus the King in late 19th- and early 20th-century France and England was due to the different degrees of influence of three conflicting but overlapping discourses: philosophy, philology and politics. It illustrates how these discourses resulted in different reception of the Greek play by the French and British TSs.